THE LATE ALBIAN GENUS SEMENOVICERAS (HOPLITIDAE, AMMONITINA): PALAEONTOLOGIC STUDY OF A FAUNA OF THE SEMENOVICERAS LITSCHKOVI ZONE FROM MANGYSHLAK (WEST KHAZAKSTAN) (Rivista italiana di Paleontologia e Stratigrafia, 1997)
The ammonites collected during an expedition to Mangyshlak in September, 1995,, are described. Three ammonitiferous levels were sampled in an arenaceous formation characterised by ferruginous, phosphatic metric concretions. The six species recognised in the two older levels belong to the genus Semenoviceras Wright, 1996 (pro Semenovites Glazunova, non  Tarbinskii, 1932), which was widespread in Central Asia mainly during the Late Albian. The third level yielded only a specimen of the mid-Cenomanian genus Cunningtoniceras, which will not be described. The second Semenoviceras -bearing level contained an extremely rich fauna of the S. litschkovi zone, S. pseudocoelonodum subzone, defined in the former Soviet Union and correlated with the Diploceras cristatum zone of western Europe. The present study allowed the intraspecific variability of Semenoviceras pseudocoelonodum (Semenov) to be defined, since the holotype was originally established on the basis of a single fragment. Furthermore, the subdivision in the subgenera Semenoviceras s. str. and Planihoplites is maintained.